Using of insurance companies ‘services for the purpose of legalization of criminal income of economic agents and avoidance of taxation - Lyeonov, Serhii; Kuzmenko, Olha; Mynenko, Serhii; Lyulyov, Oleksii (Herald of Economics, 2020)
Annotation. Providing the stable and continuous functioning of the financial services market is one of the important areas of state economic policy. Without the use of financial intermediaries, the economy cannot function. Criminals, in turn, use the weaknesses of the country’s financial system for their own illicit enrichment or the pursuit of other criminal interests. By laundering illegally obtained money, criminals destabilize the country’s financial system and expand the size of the shadow economy.The purpose of the article is to characterize the possibility of using the services of insurance companies in order to legalize the criminal income of economic agents and tax evasion by enterprises.Results. The article identifies the risk of using the services of insurance companies to legalize illegally obtained income and the place of these services in the market. The study comprehensively considered the possibility of fraudsters using the services of insurance companies to launder the illegal income of economic agents and tax evasion by enterprises. Examples of legalization of illegal income through the services of insurance companies were given. There are three main groups of insurance companies’ services: general insurance, life insurance (pension or insurance for investments), and reinsurance. The main risks associated with money laundering are inherent in each group of services. Summarizing the analysis, general recommendations for insurance companies to prevent money laundering through their services were identified.the prospects for further research. The Prospects for further research are the quantitative characterization of the risk of legalization of criminal income of economic agents and tax evasion for each group of services, as they have their own specific features.